Spatial distribution of soil carbon storage in desert shrubland ecosystems of northwest Mexico. (December 2020) - Ayala-Niño, Fernando; Maya-Delgado, Yolanda; García-Calderón, Norma E.; Olmedo, Guillermo; Guevara, Mario; Troyo-Diéguez, Enrique
Abstract: The scarce information about soil carbon (C) storage in water-stressed ecosystems limits our understanding on soil contribution to the C cycle in arid zones. This study, performed in arid NW México: (i) estimated soil capacity to store organic C (SOC) and inorganic C (SIC) linked to topography; (ii) determined the spatial distribution of regional SOC stocks; and (iii) analysed if different land-uses affect the C:N ratio. Contents of SOC from different landforms and land uses varied from <0.2 to 45 Mg ha −1 ; shallow mountain soils and alluvial plains showed the minimum and maximum values, respectively, underlying the topography relevance to soil depth. The SIC varied from <0.05 to 32 Mg ha −1, highlighting inorganic C storage. With SOC content data and environmental databases, this study achieved the regional spatial distribution of SOC stocks (0–30 cm) by predicting modelling. The average SOC stock (0–30 cm) was estimated in 25 ± 9.9 Mg ha −1 for the region. Changes in land-use from natural conditions apparently reduced N content, varying C:N ratio from 7.90 to 13.68 and reflecting the importance of land management. The results confirmed the value of arid soils to store C and their contribution to global C and N cycles. Highlights: When using global databases, generalization can under or overestimate SOC content. Geomorphic units + soil profiles offered a good estimation of SOC content. Modelling process offered a good estimation of uncertainty and SOC for the first 30 cm. Carbonates and bicarbonates in drylands soils reflected their importance as a C sequestration form.